Senegal : Request for a Three-Year Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Senegal's Request for a Three-Year Policy Coordination Instrument (PCI). The PCI for Senegal is expected to build on the lessons from the previous programs supported by the IMF. It aims to support the authorities' efforts to consolidate macroeconomic stability and foster sustained and inclusive growth. Program reviews take place on a semi-annual fixed schedule. While the PCI involves no use of IMF resources, successful completion of program reviews would help signal Senegal's commitment to continued strong economic policies and structural reforms. Although public debt has increased and the current account deficit has widened, the outlook remains favorable, provided the authorities follow through with their comprehensive reform strategy and measures to consolidate macroeconomic stability. The authorities' economic program supported by the PCI focuses on achieving high, sustainable, and inclusive growth, consolidating macroeconomic stability through prudent fiscal policy and sound debt management, and managing the oil and gas sector in a transparent manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet